Quality of dental care services and satisfaction of patients visiting dental treatment center of Kahuripan public health center, Tawang sub district, Tasikmalaya city - Anang Anang; Fitri Haryanti; Andreasta Meliala Meliala (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Patients, especially those who use health insurance have felt that the quality of primary care services tends to be less satisfying in terms of both public services and dental care services. Based on the results of the annual report at the Kahuripan Health Center, the number of patient visits to BPG decreased from 2016 to 2017 by 802 people. This study aimed to determine the quality of dental care services and the satisfaction of patients visiting BPG Kahuripan Health Center. This case study used a qualitative method and an explanatory research design. The sample in this study consisted of 40 patients as the respondents responding to the questionnaires about service quality and patient satisfaction, and 12 people were interviewed. The results showed that all dimensions of the quality of dental care services at the Kahuripan Health Center were categorized as very good i.e. real dimensions (82.71%), reliability (83.21%), responsiveness (87.12%), assurance (84.93%), and empathy (83.54%). As for patient satisfaction, three stages of patient satisfaction were categorized as very satisfied, namely the anamnesis and diagnosis stage (83.02%), action (83%), and completion of action (82.62%). The stages categorized as satisfying were the registration and waiting room stage (78.87%), and the stage of preparation of treatment (72.50%). The result of interview showed that the average respondents stated that the quality of dental care services was very good. All the five dimensions of the quality of dental care services were categorized as very good. Patients who visited BPG expressed satisfaction with the five stages, namely they were very satisfied with the three stages and satisfied with the other two stages.